NURSING CARE PATIENT BEDRIDDEN IN HOUSEHOLD: A SYSTEMATIC REVIEW (Fiep Bulletin - online, 2015)
Aimed to identify the care performed by nurses of the Family Health Strategy in relation to the patient bedridden at home. Through a systematic review on the basis of Latin American Literature data and Caribbean Health Sciences (LILACS) Scientific Electronic Library Online (SciELO), National Library of Medicine (NLM) and the Cochrane Library, with the inclusion of articles published between 2000 and 2013 are available in full and free access. Articles analyzed in the following caveats were identified: home visits and educational activities; activities related probes, tracheostomy, skin lesions, dressings; guidance regarding the organization of the home environment, nutrition and hygiene; medication administration and activities focused on comfort and pain control. It is concluded that the studies showed that the nurse performs various care related to the adaptation of the patient and their family to a new condition of life.
Keywords: nursing care; bedridden patients; Family Health Strategy.